Comparison of anterior chamber depth in healthy myopic Thai eye using orbscan and ultrasound - Chaidaroon W. (2014)
Objectives: To compare the anterior chamber depth (ACD) using ultrasonic and optical measurements. Material and Method: In this prospective study, ultrasound and optical (Orbscan) devices were employed to measure ACD in 42 eyes of 21 myopic volunteers. ACD values were compared using the paired-sample Student t test. The correlation of ACD values obtained from two groups was assessed by linear regression analysis. Results: The difference of mean ACD values between the ultrasound (3.02 ± 0.37 mm) and Orbscan (3.56 ± 0.42 mm) method was statistically significant difference (p < 0.0001). Conclusion: The optical measurement of ACD in healthy myopic Thai eyes is, on average, 0.54 mm greater than ultrasonic measurement; however, both methods posses a significant linear correlation.